Water balance assessment of different substrates on potash tailings piles using non-weighable lysimeters. (1st July 2017) - Bilibio, Carolina; Schellert, Christian; Retz, Stefanie; Hensel, Oliver; Schmeisky, Helge; Uteau, Daniel; Peth, Stephan
Abstract: Water balance is an important tool to evaluate water deficit or excess in crop systems. However, few studies have evaluated the water balance of vegetation grown on the residues from potash mining because the high sodium chloride levels of the residues hinder agricultural development. Therefore, this study aims to measure the water balance components in eight non-weighing lysimeters installed on a potash tailings pile in Heringen (Werra), Germany. These lysimeters were filled with different mixtures of household waste incineration slags and coal combustion residues, resulting in 4 different substrates with two repetitions. Manual seeding was performed using 65% perennial ryegrass ( Lolium perenne L.), 25% red fescue ( Festuca rubra L.) and 10% Kentucky bluegrass ( Poa pratensis L.). Environmental conditions were monitored using an automatic weather station; ground-level and 1-m-high rain gauges. Precipitation and drainage were recorded weekly following the initial saturation of the lysimeters. Water balance components were determined for two hydrological years based on the expression: ET (mm) = P – D, where ET = evapotranspiration, P = precipitation and D = drainage. In addition, evapotranspiration was studied using the standard FAO Penman-Monteith equation and Haude's method. The lysimeter water balance measured in 2014 revealed an actual evapotranspiration rate of 66.4% for substrate 1, 66.9% for substrate 2, 65.1% for substrate 3 and 64.1% for substrate 4. In 2015, evapotranspiration ranged from 65.7% for substrate 4 to 70.2% for substrate 1. We observed that the FAO Penman-Monteith and Haude's evapotranspiration models generally overestimated the water use of the green coverage by 67% and 23%, respectively. Our study suggests that an evapotranspiration cover for potash tailings piles may decrease brine drainage from these piles and reduce soil and water contamination. Graphical abstract: Highlights: We evaluated the water balance of eight lysimeters on a potash tailings pile. Four substrates were used to create a feasible environment for crop development. Perennial grasses evapotranspirated up to 70.2% of annual precipitation. The average drainage was 271.2 mm in 2014 and 192.1 mm in 2015. High evapotranspiration decreases brine drainage from potash tailing piles.